Cover Image, Volume 26, Issue 2. (14th January 2018) - Park, Ji Hun; Lee, Seunghwan; Song, EunHo; Shin, SangHo; Kang, ChangHo; Yoon, HyungSeok; Lee, Seunghun; Yang, JungYup; Lee, Dongho; Kim, Dongseop; Nam, Junggyu
Abstract : The cover image, by Ji Hun Park et al., is based on the Research Article Homogeneous Na incorporation for industrial‐scale application of Cu(In, Ga)(Se, S)2 solar cells, DOI:10.1002/pip.2951 .